WEB KOMIK BERBAHASA INGGRIS: Upaya Peningkatan Minat Membaca Literatur Berbahasa Inggris - Risma Fahrul Amin; Hali Makki (LP2M Universitas Ibrahimy, 2018)
Reading interest is very important in development of generation and the current issue in Indonesian education. Researchers try to carry out classroom action research that is the application of web comic to increase student’s reading interest in English literature at Ibrahimy University. The purpose of this study is to know through the application of web comic can increase student’s reading interest and reading skills and to know through the application of web comic can improve student’s reading comprehension at Ibrahimy University of Situbondo. The results of this study can be concluded that the use of web comic can increase student’s reading interest and improve student’s reading skills at Ibrahimy University of Situbondo, student’s reading comprehension also progressed from the percentage of student’s reading success from 40.63% to 93.75%.